VD_FINDINFO HC / 2019 / 762 vom 16. August 2019 - VD Tribunal cantonal (2019)
DÉCISION SUR FRAIS, CONSORITÉ, PROCÉDURE DE CONCILIATION | 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 110 CPC (CH), 113 al. 1 CPC (CH), 319 let. b ch. 1 CPC (CH)